Climate Smart Agriculture: Models for Empowering Women Livestock Producers - International Institute of Rural Reconstruction (2019)
The brief documents the experience of the International Institute of Rural Reconstruction (IIRR) and its farmer co-operator in implementing the Native Pigs Initiative in Guinayangan Climate-Smart Village in Quezon Province, Philippines. The main objective of the project is to develop an evidence-base for sustainable outscaling of climate-resilient agricultural practices to enhance livelihood, resilience, and adaptive capacities particularly in the livestock sector. CCAFS and the Department of Agriculture, through its Bureau of Agricultural Research, supported this initiative to demonstrate that small livestock are a socially relevant and economically profitable project for the poor.